2002
DOI: 10.1117/12.483036
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance free-space quantum cryptography

Abstract: Quantum cryptography bases the security of key exchange on the laws of quantum physics and will become the first application of quantum information methods. Here we present the design of novel hardware components which enabled the demonstration of secure key exchange over a 23.4 km free-space link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Hughes et al [2002] then demonstrated free-space QKD over 10 km. Free-space QKD over the largest distance so far was performed by the Munich group of H. Weinfurter (Kurtsiefer et al [2002a], Kurtsiefer et al [2002b]). Unlike the other groups, they moved to the high altitudes of the Alps to take advantage of thinner air and less air turbulence.…”
Section: Polarization Encodingmentioning
confidence: 99%
“…Hughes et al [2002] then demonstrated free-space QKD over 10 km. Free-space QKD over the largest distance so far was performed by the Munich group of H. Weinfurter (Kurtsiefer et al [2002a], Kurtsiefer et al [2002b]). Unlike the other groups, they moved to the high altitudes of the Alps to take advantage of thinner air and less air turbulence.…”
Section: Polarization Encodingmentioning
confidence: 99%
“…The theoretical properties of quantum information-processing and the feasibility of quantum communication in practical situations have been already elucidated by many experiments carried out in laboratories on the ground. In particular, recent advances in free-space experiments have allowed to achieve single-photon QKD over distances up to 23 km 10,11 and the distribution of entangled photon pairs over 600 m (Aspelmeyer et al 12 ) using optical telescopes. In the long run, the application of space and astronomical technologies to quantum communication will enable further significant increases of these distances.…”
Section: Single Photon Quantum Communicationmentioning
confidence: 99%
“…A half-wave plate before one of the PBS rotates the polarization by 451. This detection setup was used in a number of QKD demonstrations [33][34][35] .…”
Section: Methodsmentioning
confidence: 99%